Carbon ion radiotherapy: an evidence-based review and summary recommendations of clinical outcomes for skull-base chordomas and chondrosarcomas - Holtzman, Adam; Seidensaal, Katharina; Iannalfi, Alberto; Kim, Kyung Hwan; Koto, Masashi; Yang, Wan-Chin; Shiau, Cheng-Ying; Mahajan, Anita; Ahmed, Safia K.; Trifiletti, Daniel M.; Peterson, Jennifer L.; Koffler, Daniel M.; et al. (Cancers, 2023)
Skull-base chordoma and chondrosarcoma are rare radioresistant tumors treated with surgical resection and/or radiotherapy. Because of the established dosimetric and biological benefits of heavy particle therapy, we performed a systematic and evidence-based review of the clinical outcomes of patients with skull-base chordoma and chondrosarcoma treated with carbon ion radiotherapy (CIRT). A literature review was performed using a MEDLINE search of all articles to date. We identified 227 studies as appropriate for review, and 24 were ultimately included. The published data illustrate that CIRT provides benchmark disease control outcomes for skull-base chordoma and chondrosarcoma, respectively, with acceptable toxicity. CIRT is an advanced treatment technique that may provide not only dosimetric benefits over conventional photon therapy but also biologic intensification to overcome mechanisms of radioresistance. Ongoing research is needed to define the magnitude of benefit, patient selection, and cost-effectiveness of CIRT compared to other forms of radiotherapy.
Gesehen am 06.12.2023